Electrolyte Management and Monitoring to Prevent Complications MMA: A Case Report - Ali, Samin M.; Azmi, Nur; Yusanti, Irma; Priambodo, Ayu Prawesti; Mirwanti, Ristina (Indonesian Journal of Global Health Research, 2024)
Methylmalonic acidemia (MMA) is a rare metabolic disorder caused by the body's inability to break down certain proteins and fats, leading to a buildup of toxic methylmalonic acid. MMA symptoms vary and can cause serious complications if not treated appropriately. Purpose : to explanation of electrolyte management and monitoring to prevent complications on patient with methylmalonic acidemia. Method : this study used case study. Collecting data used nursing assessment. An 8 year old patient with MMA, cough accompanied by vomiting, decreased appetite, and dehydration came to the emergency room in critical condition. The patient showed signs of dehydration, metabolic acidosis, and electrolyte disturbances that required immediate treatment. Results: Management of MMA involves adequate hydration, management of hypoglycemia, correction of metabolic acidosis, and careful monitoring of electrolytes. Additional therapies such as L-Carnitine supplementation and intensive clinical monitoring are also necessary to prevent life-threatening complications. Conclusion: Rapid and appropriate treatment of the metabolic crisis in MMA is essential to prevent serious complications and improve the patient's prognosis. Regular monitoring of electrolytes and clinical parameters as well as comprehensive therapy can help improve the quality of life of individuals with MMA.